2003
DOI: 10.1097/00006534-200301000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Assisted Closure for the Treatment of Sternal Wounds: The Bridge between Débridement and Definitive Closure

Abstract: A method to refine the treatment of sternal wounds using Vacuum Assisted Closure (V.A.C.) therapy as the bridge between débridement and delayed definitive closure is described. A retrospective review of 35 consecutive patients with sternal wound complications over a 2-year period (March of 1999 to March of 2001) was performed. The treatment of sternal wounds with traditional twice-a-day dressing changes was compared with the treatment with the wound V.A.C. device. An analysis of the number of days between init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 13 publications
4
67
0
8
Order By: Relevance
“…The resulting high osmotic load destroys bacterial cells and authors have reported excellent rates of wound resolution associated with its use [34]. More recently, negative pressure dressings have been introduced and shown to be safe and effective in the management of sternal wounds [35][36][37]. However, although widely used, there are no randomised trials comparing the efficacy or costs of either of these therapies with the use of more conventional wound dressings.…”
Section: Current Treatment Of Deep Sternal Wound Infectionmentioning
confidence: 99%
“…The resulting high osmotic load destroys bacterial cells and authors have reported excellent rates of wound resolution associated with its use [34]. More recently, negative pressure dressings have been introduced and shown to be safe and effective in the management of sternal wounds [35][36][37]. However, although widely used, there are no randomised trials comparing the efficacy or costs of either of these therapies with the use of more conventional wound dressings.…”
Section: Current Treatment Of Deep Sternal Wound Infectionmentioning
confidence: 99%
“…Basic research suggests that the VAC suction pressure should be between 75 and 125 mmHg, [8][9][10] but the reservoir suction pressure of the J-VAC drainage system is around 55 mmHg. However, good results have been reported with a similar method, 7 and there were no particularly noteworthy problems in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Mediyastenitlerin cerrahi tedavisinde açık ve kapalı olmak üzere iki farklı yaklaşım uygulanmaktadır. Açık yaklaşımda debridman ve drenaj sonrası mediyasten açık bırakılmakta, cerrahi pansuman ve intravenöz antibiyotik tedavisiyle beklenen iyileşme sağlandıktan sonra geç dönemde kapatılmaktadır (1,22). Bu yöntemin dezavantajları, toraksın mekanik desteğinin olmaması nedeniyle gelişen solunum yetmezliği, vasküler yapıların bütünlüğünün bozulması ve gecikmiş doku iyileşmesi olarak sıralanabilir (1).…”
Section: Tedaviunclassified